Regulatory Forum Opinion Piece: Review—Toxicological Pathology Profile and Regulatory Expectations for Nonclinical Development of Insulins and Insulin Analogues. (October 2016) - Bartels, Thomas; Wäse, Kerstin; Heinrichs, Martin; Stolte, Manuela; Roome, Nigel; Scherer, Petra; Lindauer, Klaus
The toxicological profile of insulins is exclusively due to exaggerated pharmacology resulting in hypoglycemic findings. Insulin analogues displaying modifications and aimed at improving pharmacokinetics do not induce different toxicity. The main target is the brain displaying neuronal necrosis. Wallerian degeneration of nerves occurs rarely after severe hypoglycemia. These findings are of potential human relevance; nevertheless, these changes are induced in normoglycemic animals whereas diabetic patients suffer from hyperglycemia. Therefore, it is usually not difficult to achieve a therapeutic window for subsequent use in patients. Based upon this and in the absence of classical toxicity, there has been no scientific need for diabetic animal models. A greater challenge is the mitogenicity already inherent with regular insulin. Thus, the focus for preclinical safety evaluation of analogues is to demonstrate that modifications in regular insulin do not result in enhanced mitogenicity. The approaches used to assess the mitogenic potential of insulin analogues have changed over time driven by scientific progression and changes within the regulatory environment. Therefore, in vitro and in vivo evaluation of cell proliferation has become common practice, and to date there has been no evidence that the mitogenic potential of insulin analogues may be increased compared to regular insulin.